Updated analyses of temperature and precipitation extreme indices since the beginning of the twentieth century: The HadEX2 dataset - Donat, M. G. (2013)
In this study, we present the collation and analysis of the gridded land-based dataset ofindices of temperature and precipitation extremes: HadEX2. Indices were calculated based onstation data using a consistent approach recommended by the World Meteorological Organization (WMO) Expert Team on Climate Change Detection and Indices, resulting in theproduction of 17 temperature and 12 precipitation indices derived from daily maximum andminimum temperature and precipitation observations. High-quality in situ observations fromover 7000 temperature and 11,000 precipitation meteorological stations across the globe wereobtained to calculate the indices over the period of record available for each station. Monthlyand annual indices were then interpolated onto a 3.75 x 2.5 longitude-latitude grid over theperiod 1901–2010. Linear trends in the gridded ﬁelds were computed and tested for statisticalsigniﬁcance. Overall there was very good agreement with the previous HadEX dataset duringthe overlapping data period. Results showed widespread signiﬁcant changes in temperatureextremes consistent with warming, especially for those indices derived from daily minimumtemperature over the whole 110 years of record but with stronger trends in more recentdecades. Seasonal results showed signiﬁcant warming in all seasons but more so in the coldermonths. Precipitation indices also showed widespread and signiﬁcant trends, but the changeswere much more spatially heterogeneous compared with temperature changes. However,results indicated more areas with signiﬁcant increasing trends in extreme precipitationamounts, intensity, and frequency than areas with decreasing trends